Charakter prawny pozwoleń na prowadzenie indywidualnej działalności gospodarczej - Waligórski, Michał (Wydział Prawa i Administracji UAM, 1988)
The article is concerned with one of basic institutions of administrative law, i.e. the licenses for carrying out individual economic activity. The author presents regulative activités of State administration organs in the sphere of individual economy, pointing out to the need of reducing those activities and replacing them with economic mechanisms. In Poland the main form of regulative activities of State administration organs with respect to private sector is granting licenses for carrying out handicraft, trade and services. The author, discussing the premisses of granting and withdrawing licenses in the light of the legislation in force and the decisions of the Chief Administration Court, points to the need of making it easier to start and carry out individuai economic activity through eliminating the existing formal and administrative obstacles. The author systematizes the regulative means used by State administration organs in the domain of private economic activity and discusses their legal character of constitutive administrative acts licensing and legalizing the economic activity of a specific kind within the whole of the economic relations in the country
Legal character of licences for carrying out individual economic activity